Electronic cash system based on certificateless group signature - Yan LIANG; Xiao ZHANG; Zhi-ming ZHENG (Tongxin xuebao)
An efficient elliptic certificateless group signature ith forward security and member revocation based on ACJT group signature was proposed.Compared to ACJT which has complex computation,many parameters and long signature length,proposed scheme has less parameters and only involve a small amount of computation.The length of proposed signature is short and the efficiency is high.A fair off-line multi-bank e-cash system based on this group signa-ture scheme was also proposed.The new e-cash system has not only the high security and efficiency,but the unforgeabil-ity.It also can avoid double-spending and tampering money.The scheme has a clear advantage compared with others.